Werewere Liking, Vicky Tsikplonou e Adama Lucie Bacco: female artists appropriating puppetry to empower women in West Africa (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
In this article, researcher Denyer problematizes the role of women in West African puppetry based on the trajectories and interviews with African artists Liking, Tsikplonou and Bacco. She reports and analyzes their practices in the African puppetry groups Ki-Yi Puppets & Dances, Evago and Bouam, respectively, showing that these women created new ways of thinking about puppet theater in Africa. According to Denyer, they have created post-traditional figures in puppetry who overturn cultural expectations and raise awareness of issues such as health, education and social prejudices during their performances.
Keywords: West Africa; puppetry; women; African groups